2016
DOI: 10.1002/aic.15198
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature pyrolysis and CO2 gasification of Victorian brown coal and Rhenish lignite in an entrained flow reactor

Abstract: The low rank coals from Victoria, Australia, and Rhineland, Germany are of interest for use in entrained flow gasification applications. Therefore, a high temperature, electrically heated, entrained flow apparatus has been designed to address the shortage of fundamental data. A Victorian brown coal and a Rhenish lignite were subjected to rapid, entrained flow pyrolysis between 1100 and 14008C to generate high surface area chars, which were subsequently gasified at the same temperatures under CO 2 in N 2 betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 24 publications
(35 reference statements)
2
32
0
Order By: Relevance
“…The Zhundong subbituminous char specific surface area slightly increases from 15 to 37 m 2 /g with temperature increasing from 500 to 600°C, then decreases to 15 m 2 /g with temperature further increasing to 800°C, and finally rapidly increases to 78 m 2 /g at 1,000°C . However, for various coals, a decreasing char surface area with increase of temperature during slow pyrolysis is observed at temperatures above 1,200 K …”
Section: Introductionmentioning
confidence: 94%
“…The Zhundong subbituminous char specific surface area slightly increases from 15 to 37 m 2 /g with temperature increasing from 500 to 600°C, then decreases to 15 m 2 /g with temperature further increasing to 800°C, and finally rapidly increases to 78 m 2 /g at 1,000°C . However, for various coals, a decreasing char surface area with increase of temperature during slow pyrolysis is observed at temperatures above 1,200 K …”
Section: Introductionmentioning
confidence: 94%
“…In this study, CO/CO 2 and K as main fragment of potassium species was qualitatively and semi-quantitatively measured. The reduction of CO 2 by the glycol and carbon of the char during the reaction results in the formation of CO [23]. Thus, the start and the end of reaction of the glycol and char can be identified.…”
Section: Gas Analysis (Mbms)mentioning
confidence: 99%
“…3,10,11 An estimated 22% higher thermal efficiency and 25% lower CO 2 emission is reported using black coal in an integrated gasification combined cycle (IGCC) power plant, resulting in the lower CO 2 emission of 370 kg/MWh e . 7,12 Numerous studies [13][14][15][16][17][18][19] have been conducted to investigate the entrained flow gasification of coal and biomass using air, oxygen, steam and CO 2 . The results of CO 2 gasification showed that the yield of CO increases whereas H 2 decreases with increasing CO 2 -to-coal ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies 13‐19 have been conducted to investigate the entrained flow gasification of coal and biomass using air, oxygen, steam and CO 2 . The results of CO 2 gasification showed that the yield of CO increases whereas H 2 decreases with increasing CO 2 ‐to‐coal ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation